Implementation of a Web-Based Village Information System Using the Waterfall Method in Hegarmukti Village - Ferdiansyah, Febby; Anshor, Abdul Halim; Widodo, Edy (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The dissemination of information at the village level is crucial for ensuring transparency to the residents. To facilitate the quick and easy communication of such information, a web-based village information system was developed. This system can be accessed by all community members, both within and outside the village, as long as they have an internet connection. Currently, Hegarmukti Village does not have an effective web-based information system, leading to delays in information delivery and a lack of accuracy. Moreover, the potential of the village remains under-promoted. This study aims to design and implement a web-based village information system for Hegarmukti Village using the Waterfall method. The system is developed using HTML for programming and MySQL for the database, with the goal of enhancing transparency and the efficiency of information dissemination. The system provides features such as village profiles, news updates, and population data searches, improving the accessibility and reliability of village information.